2020
DOI: 10.1186/s12879-020-05404-w
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterisation and antimicrobial resistance of Pseudomonas aeruginosa strains isolated from patients of different hospitals and medical centres in Poland

Abstract: Background Pseudomonas aeruginosa is a Gram-negative bacteria responsible for infections in immunocompromised patients and is one of the most common causes of nosocomial infections particularly in intensive care and burn units. We aimed to investigate the population structure of P. aeruginosa strains isolated from patients at different hospital wards. Methods: We analysed the possible presence of P. aeruginosa epidemic or endemic strains in hospitals of the selected region. A genotyping analysis was performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
1
14
0
2
Order By: Relevance
“…Previous studies from Iran have approved the high resistance rates of the P. aeruginosa to a wide range of antibiotics, which was similar to current results 19 , 20 . In contrast to these findings, Brzozowski et al 21 from Poland reported a lower resistance rates for ciprofloxacin (39.1%), amikacin (30.7%), cefepime (42.6%), ceftazidime (33.2%), gentamycin (37.6%), piperacillin/tazobactam (39.6%), tobramycin (38.1%), and imipenem (67.8%) in clinical P. aeruginosa . These discrepancies could be due to differences in the geographical regions and diversity of antibiotic prescription patterns, as well as the lack of a comprehensive and organized monitoring program for the proper use of antibiotics in several countries.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies from Iran have approved the high resistance rates of the P. aeruginosa to a wide range of antibiotics, which was similar to current results 19 , 20 . In contrast to these findings, Brzozowski et al 21 from Poland reported a lower resistance rates for ciprofloxacin (39.1%), amikacin (30.7%), cefepime (42.6%), ceftazidime (33.2%), gentamycin (37.6%), piperacillin/tazobactam (39.6%), tobramycin (38.1%), and imipenem (67.8%) in clinical P. aeruginosa . These discrepancies could be due to differences in the geographical regions and diversity of antibiotic prescription patterns, as well as the lack of a comprehensive and organized monitoring program for the proper use of antibiotics in several countries.…”
Section: Discussionmentioning
confidence: 81%
“…In another study, isolates of P. aeruginosa revealed 50%, 63.9%, 16.7%, 8.3%, and 16.7% resistance to imipenem, cefepime, amikacin, tobramycin, gentamicin, respectively which is lower than the current study ( 31 ). Brzozowski et al reported lower rate of resistance to imipenem and cefepime and higher rate of resistance to tobramycin, amikacin, and gentamicin ( 32 ). Recently, phage therapy was studied as one of the renewed biologic approaches to combat multi-drug resistant bacteria in therapeutic fields.…”
Section: Discussionmentioning
confidence: 99%
“…The history of P. aeruginosa and S. marcescens cultured bronchoscopy in Poland is surprising as these are generally nosocomial respiratory infections. 1,2 The patient did not have risk factors for communityacquired pneumonia with P. aeruginosa or other gram-negative bacteria, such as pulmonary disease or previous hospital admission, antibiotic use 3 or oral steroid use.…”
Section: Discussionmentioning
confidence: 99%